The Impact of Interactive MRI-Based Radiologist Review on Radiotherapy Target Volume Delineation in Head and Neck Cancer - Adjogatse, D.; Petkar, I.; Reis Ferreira, M.; Kong, A.; Lei, M.; Thomas, C.; Barrington, S.F.; Dudau, C.; Touska, P.; Guerrero Urbano, T.; Connor, S.E.J. (American Journal of Neuroradiology, 2023)
BACKGROUND AND PURPOSE: Peer review of head and neck cancer radiation therapy target volumes by radiologists was introduced in our center to optimize target volume delineation. Our aim was to assess the impact of MR imaging-based radiologist peer review of head and neck radiation therapy gross tumor and nodal volumes, through qualitative and quantitative analysis.MATERIALS AND METHODS: Cases undergoing radical radiation therapy with a coregistered MR imaging, between April 2019 and March 2020, were reviewed. The frequency and nature of volume changes were documented, with major changes classified as per the guidance of The Royal College of Radiologists. Volumetric alignment was assessed using the Dice similarity coefficient, Jaccard index, and Hausdorff distance.RESULTS: Fifty cases were reviewed between April 2019 and March 2020. The median age was 59 years (range, 29–83 years), and 72% were men. Seventy-six percent of gross tumor volumes and 41.5% of gross nodal volumes were altered, with 54.8% of gross tumor volume and 66.6% of gross nodal volume alterations classified as “major.” Undercontouring of soft-tissue involvement and unidentified lymph nodes were predominant reasons for change. Radiologist review significantly altered the size of both the gross tumor volume (P  = .034) and clinical target tumor volume (P  = .003), but not gross nodal volume or clinical target nodal volume. The median conformity and surface distance metrics were the following: gross tumor volume Dice similarity coefficient = 0.93 (range, 0.82–0.96), Jaccard index = 0.87 (range, 0.7–0.94), Hausdorff distance = 7.45 mm (range, 5.6–11.7 mm); and gross nodular tumor volume Dice similarity coefficient = 0.95 (0.91–0.97), Jaccard index = 0.91 (0.83–0.95), and Hausdorff distance = 20.7 mm (range, 12.6–41.6). Conformity improved on gross tumor volume-to-clinical target tumor volume expansion (Dice similarity coefficient = 0.93 versus 0.95, P  = .003).CONCLUSIONS: MR imaging–based radiologist review resulted in major changes to most radiotherapy target volumes and significant changes in volume size of both gross tumor volume and clinical target tumor volume, suggesting that this is a fundamental step in the radiotherapy workflow of patients with head and neck cancer.AJCCAmerican Joint Committee on CancerCTVclinical target volumeCTVNclinical target nodal volumeCTVTclinical target tumor volumeDSCDice similarity coefficientGTVgross target volumeGTVNgross nodal volumeGTVoncoriginal oncology GTVGTVradpostradiology review volumeGTVTgross tumor volumeHDHausdorff distanceHNhead and neckHNChead and neck cancerIQRinterquartile rangeJIJaccard indexPTVplanning target volumeRTradiotherapyTREtarget registration error